An outbreak of Salmonella enteritidis phage type 34a infection in primary school children: the use of visual aids and food preferences to overcome recall bias in a case control study - LINNANE, E.; ROBERTS, R. J.; MANNION, P. T. (Epidemiology and infection, 2002)
Outbreaks of infectious intestinal disease are common in schools. Case control studies are useful in the investigation of infectious disease outbreaks but the time interval between illness and investigation can lead to recall bias, particularly in young children. We describe an outbreak of Salmonella enteritidis phage type 34a infection involving 54 clinical cases in two adjacent schools, and a novel approach to overcome recall bias. The likely dates of infection were identified from the epidemic curve. We created a visual display of the menu from those days and asked 9 cases and 18 matched controls to identify their food preferences from this display. Preference for chocolate mouse was significantly associated with illness (P = 0.006). The results of the case control study agreed with the findings of the environmental investigation. We believe our approach could be used in other circumstances, where subjects are young children or recall bias is a concern.